The Complexities of Interpreting in Refugee Contexts: An Examination of Issues and Practice - Crezee, I; Hayward, M; Julich, S (AUT Tangible Media, 2011)
Interpreters working with refugees experience a complex working environment. They are sometimes required to interpret traumatic material, and those who are refugees themselves might be coping with their own traumatic histories or Post Traumatic Stress Disorder (PTSD). This paper reports the results of a survey that investigates the interpreting experience and the vulnerability of interpreters to vicarious traumatisation or re-traumatisation. Further, it investigates the training and preparation of interpreters who are working in such environments and explores the requirements of other professionals involved with these interpreters.
Keywords: Interpreting in refugee settings; health interpreting; Vicarious traumatisation; Retraumatisation